Die (Un-)Verständlichkeit von Gesetzen – eine Herausforderung für die Gesetzesredaktion - Lötscher, Andreas (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2016)
It is a generally acknowledged truth that laws must be comprehensible. However, according to the prevailing view among jurists, it is impossible to fulfil this requirement because laws, as shown by the practice of legal interpretation, do not have a precisely defined meaning. Based on this premise, this article addresses the question of how comprehensibility can be made possible when formulating legal norms. The answer requires a precise understanding of the processes of comprehension, of the conditions for comprehending texts and of the relations between the meaning of a text, comprehension of a text and legal interpretation.